Beyond 'Science and Theology': How Science Might Contribute to Theological Understanding. Issue 2 (1st April 2021) - Messer, Neil
Abstract : Methodological questions about the interactions of theology with the sciences have often been framed as the relationship between 'science and theology', understood as two distinct and monolithic entities. This paper offers a different way to think about these interactions by asking how scientific insights should contribute to theological understanding of particular questions. With reference to a particular case study – the scientific study of religion – five types of theological engagement with science are explored, and conclusions drawn about the merits of each.